Implementation of the Team Assisted Individualization (TAI) Cooperative Learning Model to Improve Student Learning Outcomes on Hydrocarbon Topics in Grade XI at State Senior High School - Nazira, Relfa; Abdullah, Abdullah; Herdini, Herdini (Journal of The Indonesian Society of Integrated Chemistry, 2025)
This study aims to examine the effectiveness of the Team-Assisted Individualization (TAI) cooperative learning model in improving the learning outcomes of Grade XI students on hydrocarbon material at State Senior High School 2 Dumai. The research employed a randomized control group pretest-posttest design, involving two groups selected randomly, an experimental group that applied the TAI model and a control group that used discussion-based learning. A test on hydrocarbon concepts was administered to both groups before and after the treatment to measure student performance. The data were analyzed using a t-test at a 0,05-significance level. The results showed that the calculated t-value of 5,24023 exceeded the t-table value of 1,6664, indicating a significant difference in learning outcomes between the two groups. These findings suggest that the cooperative learning type of the Team Assisted Individualization is more effective in enhancing the learning outcomes of students compared to the discussion method previously used in the class. Keyword:        Cooperative model, hydrocarbons, learning outcomes, team assisted individualization.